2008
DOI: 10.1007/s10815-008-9263-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GnRH down-regulation on cumulus cell viability and apoptosis as measured by fluorescence-activated cell sorting

Abstract: Objective To determine whether gonadotropin releasing hormone (GnRH)-agonist or -antagonist induces higher percentages of cumulus cell apoptosis and if the use of either is detrimental to ART outcomes. Patients Women in a private facility under treatment for IVF had their cumulus cells isolated and analyzed by flow cytometry. Viable, apoptotic, and dead cumulus cell rates related to ovarian stimulation by GnRH-agonist orantagonist were measured and compared with fertilization and implantation rates. Results Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Cumulus cells are thought to play an important role in oocyte maturation and fertilization, with signaling and regulation of functions (3). Many studies have shown us that oocyte quality and fertilization potential are related to the rate of granulosa cell apoptosis in women receiving in vitro fertilization (IVF) treatment (7). It has also been shown that granulosa and cumulus cells play an important role in oocyte maturation due to cell-cell relationship, therefore the emergence of apoptosis or necrosis in granulosa cells may be associated with future embryo quality and poor IVF/ Intracytoplasmic sperm injection (ICSI) outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulus cells are thought to play an important role in oocyte maturation and fertilization, with signaling and regulation of functions (3). Many studies have shown us that oocyte quality and fertilization potential are related to the rate of granulosa cell apoptosis in women receiving in vitro fertilization (IVF) treatment (7). It has also been shown that granulosa and cumulus cells play an important role in oocyte maturation due to cell-cell relationship, therefore the emergence of apoptosis or necrosis in granulosa cells may be associated with future embryo quality and poor IVF/ Intracytoplasmic sperm injection (ICSI) outcomes.…”
Section: Introductionmentioning
confidence: 99%